Business intelligence for decision-making in royalties project management (2025)
This article highlights the critical role of specialized digital tools in enhancing project management and monitoring in Colombia's public sector, it showcases how Microsoft Office 365 and Power Platform have been effectively utilized to optimize royalty-funded initiatives, automating processes and improving decision-making through advanced data análisis. These tools enable process optimization, task automation, and enhanced data analysis, significantly improving the administration of resources and facilitating timely, well-informed decision-making. The methodology is quantitative and complementary information is taken from the technical and legal opinions of the participating professionals. For its execution, a combined approach had to be followed: a PMBOK methodology that gave a clear roadmap and an agile SCRUM methodology capable of highly prioritizing schedule management to provide effective results. In this process, the tools used are Power BI, Power Apps, and Power Automate; these are used to automate tasks and improve operational efficiency by addressing specific issues and contributing to project management and project optimization. Through this project, a proper technological infrastructure has been built for senior management strategic management, planning team tactical management, and operative monitoring to implement BI systems successfully. The project is structured in several phases: initial preparation and planning; implementation; and personnel training, emphasizing continuous training and personnel adaptation to manage resistance to change. Implementing BI and digital tools facilitates teams to work closely together, with noticeable improvements in coordination and operational efficiency. This paper deals with the optimization of monitoring project management of the SGR in the Office of the Attorney General of the Nation, and this experience seeks to be an example to other entities and to inspire them to walk these paths toward a culture of innovation and permanent improvement within the public sector in Colombia. These Microsoft tools are available to most national public servants and contractors, so generating the solution does not imply additional costs. The experience is well documented in the present work and provides a replicable model that can adapt to multiple contexts, promoting greater efficacy and efficiency in public administration.